The LH–DH module of bacterial replicative helicases is the common binding site for DciA and other helicase loaders. Issue 2 (10th February 2023) - Cargemel, Claire; Marsin, Stéphanie; Noiray, Magali; Legrand, Pierre; Bounoua, Halil; Li de la Sierra-Gallay, Inès; Walbott, Hélène; Quevillon-Cheruel, Sophie
Abstract : The crystallographic structure of the DnaB·DciA complex from Vibrio cholerae reveals that the various helicase loaders share the same binding site on the bacterial replicative helicase, albeit with differences in their loading mechanisms. Abstract : During the initiation step of bacterial genome replication, replicative helicases depend on specialized proteins for their loading onto oriC . DnaC and DnaI were the first loaders to be characterized. However, most bacteria do not contain any of these genes, which are domesticated phage elements that have replaced the ancestral and unrelated loader gene dciA several times during evolution. To understand how DciA assists the loading of DnaB, the crystal structure of the complex from Vibrio cholerae was determined, in which two Vc DciA molecules interact with a dimer of Vc DnaB without changing its canonical structure. The data showed that the Vc DciA binding site on Vc DnaB is the conserved module formed by the linker helix LH of one monomer and the determinant helix DH of the second monomer. Interestingly, DnaC from Escherichia coli also targets this module onto Ec DnaB. Thanks to their common target site, it was shown that Vc DciA and Ec DnaC could be functionally interchanged in vitro despite sharing no structural similarity. This represents a milestone in understanding the mechanism employed by phage helicase loaders to hijack bacterial replicative helicases during evolution.